All these poses, such beautiful poses: Articulations of queer masculinity in the music of Rufus Wainwright - Jones, Matthew J. (Université de Géorgie, 2008)
Singer-composer Rufus Wainwright uses specific musical gestures to reference historical archetypes of urban, gay masculinity on his 2002 album Poses. The cumulative result of his penchant for pastiche, eschewal of traditional musical boundaries, and self-described hedonism, Poses represents Wainwright's direct engagement with the politics of identity and challenges dominant constructions of (homo)sexuality and masculinity in popular music. Drawing from a vast lexicon of musical styles, he assembles an idiosyncratic persona, ignoring several decades of pop with an "utter lack of machismo [and] a freedom that comes to outsiders disinterested in meeting the requirements of the dreary status quo." Though analysis of musical and lyrical characteristics of Poses, I establish a dialectic between Wainwright's musical persona and four historical modes of urban gay masculinity: the 19th Century English Dandy, the French flaneur, the 20th Century gay bohemian, and the "Clone." In doing so, I introduce Wainwright as a reinvigorating force, resuscitating the subversive potential of radical gay sexuality as a 21st Century model for imagining gay male subjectivity.
https://esploro.libs.uga.edu/esploro/outputs/9949334528002959
Keywords: 2000 à aujourd'hui; 2000-2009; DIG; approches et analyses; arts; culture populaire; discipline; discours dominant; ethnographie; genre; hétérosexisme; masculinité; musique; mémoires/thèses; périodes historiques; queer; ressource en ligne; systèmes d'oppressions

The conservation of a gender fantasy: Women and Top 40 radio in Montreal - Maki, Christine (Université McGill, 2008)
Cette thèse fait l'analyse de la radio anglophone « Top 40 » à Montréal, en mettant l'accent sur la sexospécificité des animateurs et des auditeurs. En étudiant l'histoire de la radio commerciale, et les liens entre la radio et les femmes, ce travail démontre que les postes de radio ne faisaient pas plus que maintenant une programmation basée sur une compréhension réelle de leurs auditeurs, mais plutôt sur une idée virtuelle de leur auditoire-cible. Ceci traduit une manière conservatrice d'imaginer un auditoire féminin et une programmation qui ne respecte pas réellement les vrais intérêts des femmes.
https://escholarship.mcgill.ca/concern/theses/td96k5303
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; communication; culture populaire; discipline; discours dominant; genre; montréal; mémoires/thèses; périodes historiques; radio; ressource en ligne; régions géographiques; sexisme; stéréotypes de genre; systèmes d'oppressions

Gay, lesbian, bisexual, and transgendered literature: A genre guide - Bosman, Ellen; Bradford, John P. (Libraries Unlimited, 2008)
Voici un guide de genre attendu depuis longtemps sur un corpus littéraire jusqu’alors ignoré. Le livre vise à fournir au lecteurice et aux conseiller.è.s de lecture une introduction à la littérature gay, lesbienne, bisexuelle et transgenre du XXe siècle. Tous les genres littéraires populaires sont examinés, y compris la fiction, le théâtre et les récits de vie (biographie, autobiographie et mémoires), l'accent étant mis sur la fiction actuelle. Plus de 1 100 titres sont organisés selon les genres, sous-genres et formats. Les annotations fournissent des résumés brefs et captivants de l'intrigue, des informations sur les récompenses, des indications sur les populations concernées (par exemple, les gays, les lesbiennes, les adolescent.e.s) et souvent des suggestions pour les lecteurices identiques. Des termes de sujet ou des mots-clés accompagnent chaque entrée pour améliorer l'accès à davantage de lectures similaires.
Keywords: 1900-1999; arts; discipline; identités LGBTQIA2+; littérature; outils; ouvrages de références; périodes historiques; études littéraires

"Eskimo chicks and word warriors": The creative cultural spaces of Elisapie Isaac and Taqralik Partridge - Foot, Johanna Maria (Université Carleton, 2008)
For this study, I have interviewed fourteen women composers of electroacoustic music in or near the three Canadian urban centres of Montreal, Toronto, and Vancouver. Montreal: Ciaire Pich6, Lucie Jasmin, Pascale Trudel, Monique Jean, Helen Hall and Kathy Kennedy; Toronto: Gayle Young, Sarah Peebles, Wende Bartley, Elma Miller, Ann Southam, and Carol Ann Weaver; Vancouver: Hildegard Westerkamp and Susan Frykberg. These interviews were all conducted between January and November of 1993. References to the development of electroacoustic music in Canada are sparse in the existing literature, both in general histories of electroacoustic music, and in histories of Canadian music. And even though there seem to be some areas of change (for instance, recent publications in Quebec), women composers are under-represented in writings and recorded collections of electroacoustic music in Canada. Chapter Two situates the work of women composers in the Canadian scene, discussing particularly the work of Norma Beecroft, Marcelle Desch§nes, Diana McIntosh, and Micheline Coulombe Saint-Marcoux. Chapter Three describes the metaphors, images and myths invoked in malestream discourses associated with electroacoustic music, in popular magazines, course texts and software. I investigate how my consultants’ language reflects and/or contests mainstream imagery, or how it might be framed by entirely different assumptions and experiences. Chapter Four is concerned with the institutional structures of electroacoustic music. I discuss how gendering exhibits itself in the division of labour in electroacoustic studio courses at universities, as well as in concert halls, conferences, and professional organizations. Excerpts from the interviews record my consultants experiences in these institutions, as students, teachers, and composers. In Chapter Five, I point out the variety of strategies that each composer uses to construct her identity within the world of electroacoustics. Each entry takes the form of a three or four page sketch, with quotes from the interview regarding the social environment, equipment choices, compositional styles, and particular pieces that my consultant discusses. Chapter Six discusses three pieces in detail: one by Susan Frykberg, Woman and House; one by Wende Bartley, A Silence Full of Sound; and one by Hildegard Westerkamp, Breathing Room. I focus on how each of the composers chooses to work with technology, and how her culturally-constructed position as a woman affects her work. I describe how my consultants imagine other stories to tell, and other possible lived social relations. The conclusions in Chapter Seven, in addition to suggesting areas for future research, discuss three themes that run throughout the study: the idea of gender as performance, the doubleness of my consultants' responses to technology, and the importance of the linguistic and musical metaphors that they use.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; arts; canada; discipline; femmes* autochtones; mémoires/thèses; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Butch/Femme differences in substance use and abuse among young lesbian and bisexual women: Examination and potential explanations. - Rosario, Margaret; Schrimshaw, Eric W; Hunter, Joyce (Substance use & misuse, 2008)
The current study examined the role of gender atypical self-presentation on the alcohol, tobacco, and marijuana use, as well as symptoms of substance abuse/misuse, of an ethnically diverse sample of 76 young (ages 14-21 years) lesbian and bisexual women who were interviewed between 1993 and 1995 in New York City. Even after controlling for age, sexual identity, and social desirability, young butch women reported drinking alcohol more frequently and in greater quantity, smoking more cigarettes, and using marijuana more frequently than young femme women. Experiences of gay-related stressful events, internalized homophobia, and emotional distress were found to largely account for the butch/femme differences in tobacco and marijuana use, but not in higher levels of alcohol use. Despite the small convenience sample, these findings suggest that intervention efforts to address the higher levels of substance use among young lesbian and bisexual women may increase effectiveness by also addressing experiences of gay-related stress and emotional distress of young butch women. The study's limitations are noted
Keywords: 1900-1999; 1990-1999; amériques; identités LGBTQIA2+; personnes bisexuelles; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; santé; thématiques; états-unis

Gender inequity in health: Why it exists and how we can change it - Sen, G.; Östlin, P. (Global Public Health, 2008)
Ce supplément spécial de Global Public Health rassemble les versions courtes de huit revues, rédigées en 2007, dans le cadre des travaux du Women and Gender Equity Knowledge Network (WGEKN) de la Commission des déterminants sociaux de la santé (CSDH) de l'Organisation mondiale de la santé (OMS). Les auteurs de cette introduction étaient les coordinateurs du WGEKN, créé en 2006 et financé par le ministère suédois des Affaires étrangères par l'intermédiaire de l'OMS, l'Institut national suédois de la santé publique (SNIPH) et la Fondation Open Society Institute (Zug). La tâche du WGEKN était de synthétiser les connaissances et d'élaborer des recommandations sur les mécanismes, les processus et les mesures qui peuvent être mis en œuvre pour réduire les inégalités entre les sexes en matière de santé. Les recommandations du WGEKN sont incluses dans ce numéro de la revue en annexe. Le rapport final du WGEKN (Sen et al.Citation2007 ) a été soumis au CSDH en septembre 200
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; inégalités; inégalités hommes-femmes; projet charge mentale; périodes historiques; rapports sociaux de sexe; santé; systèmes d'oppressions; thématiques

Tongues on fire Caribbean lesbian lives and stories - Elwin, Rosamund (Women's Press, 2008)
In Tongues on Fire, Caribbean lesbians speak zami desire honestly and eloquently, loudly and clearly. Narrating their life stories, they claim what has never been acknowledged―lesbian history and continuity in the Caribbean. They collectively honour that history and continuity in fiction sweet with intimacy, sensuality, and memory. Like the lives and stories of Caribbean lesbians, Tongues on Fire is unique. Rosamund Elwin has put together a fine collection that includes well-known writers such as Michelle Cliff, Shani Mootoo, and Makeda Silvera.
Keywords: amériques; arts; caraïbes; discipline; histoire et politique; personnes lesbiennes; ressource en ligne; roman; régions géographiques; sexualité; thématiques; émotions; études littéraires

Women and media: A critical introduction - Byerly, Carolyn M.; Ross, Karen (John Wiley & Sons, 2008)
Women and Media is a thoughtful cross-cultural examination of the ways in which women have worked inside and outside mainstream media organizations since the 1970s. Rooted in a series of interviews with women media workers and activists collected specifically for this book, the text provides an original insight into women’s experiences. Explains the ways that women have organized their internal and external campaigns to improve media content (or working conditions) for women, and established womenowned media to gain a public voice. Identifies key issues and developments in feminist media critiques and interventions over the last 30 years, as these relate to production, representation and consumption. Functions as both a research case study and a teaching text.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; cinéma; communication; discipline; histoire et politique; médias; projet charge mentale; périodes historiques; ressource en ligne; thématiques; travail

Gender and interpersonal violence: Language, action and representation - Alexander, Flora; Throsby, Karen (Palgrave Macmillan, 2008)
S'appuyant sur des recherches contemporaines issues de l'ensemble des sciences sociales et humaines, y compris des contributions de la sociologie, de l'histoire, de la psychologie, des études cinématographiques et des études des médias, ce recueil édité illustre la manière dont les formes de violence interpersonnelle et sa genrification sont conceptualisées, interprétées, combattues et adoptées dans différents contextes et disciplines. De plus, il explore le rôle du langage dans la facilitation et la contrainte de la « dicibilité » de la violence interpersonnelle, montrant comment ces formes de violence sont devenues indicibles - excluant et réduisant au silence les personnes qui subissent la violence. En examinant à la fois les expériences vécues de la violence et les représentations de la violence, ce recueil souligne la nécessité de nouvelles façons d'articuler et de conceptualiser la violence interpersonnelle genrée dans toutes ses manifestations.
Keywords: cours; discipline; sciences humaines; sociologie; thématiques; trs3500; violence interpersonnelle; violences; violences genrées; violences sexistes

"Because she was my first girlfriend, I didn't know any different": Making the case for mainstreaming same‐sex sex/relationship education - Donovan, Catherine; Hester, Marianne (Sex Education, 2008)
In this paper we present the case for those entering/considering same-sex relationships to be included in sex and relationship education in schools. The Government's Guidance on Sex and Relationship Education provides a rationale for including same-sex relationships when it says that schools should meet the needs of all their pupils "whatever their developing sexuality." Research on sex education and domestic violence prevention for schools has highlighted issues of gender, power, the importance of understanding context in providing skills and knowledge for safer sex and non-abusive relationships. However, both tend to assume the context is heterosexuality. Results from our Economic & Social Research Council-funded study of domestic violence in same-sex and heterosexual relationships indicates that those aged under 25 years of age and those in first same-sex relationships are particularly vulnerable to experiencing domestic violence. Four themes arise from the qualitative data that provide a rationale for the provision of sex and relationship education to these young people: first same-sex relationships as an affirmation of identity; and lack of knowledge about what to expect in same-sex relationships; of embeddedness in lesbian, gay, bisexual, transgender and queer friendship networks; and of resources to seek help.
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; LGBTQIA2+; approches et analyses; discours dominant; genre; hétérosexisme; identités LGBTQIA2+; inégalités; périodes historiques; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; violences; violences conjugales; éducation sexuelle; étude qualitative

Mental illness as social product or social construct: a contradiction in feminists’ arguments? - Busfield, Joan (Sociology of Health & Illness, 2008)
Feminists have been taken to task for suggesting both that the higher level of mental illness observed in women is a consequence of the oppression they face - an oppression which drives them into madness and mental disorder - and also that the concept of mental illness is a social construct inappropriately and incorrectly applied to women by a patriarchal order as a means of social control. This paper examines this supposed contradiction and the ideas that underly the contrasting contentions. It argues that the two positions are not in fact incompatible.
Number: 4
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; inégalités; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; santé mentale; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Engaging islamic feminism: Provincializing feminism as a master narrative - Barlas, Asma (Islamic feminism: Current perspectives, 2008)
https://images.shulcloud.com/14262/uploads/Jeannettes-Class-Documents/WeekThree/EngagingIslamicFeminism.pdf
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discours dominant; fem3400; féminisme islamique; premier cycle; périodes historiques; ressource en ligne; systèmes d'oppressions

Book Review: Making Space for Indigenous Feminism - Charron, Nadine (Gender and Development, 2008)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; critique de livre; féminisme autochtone; histoire et politique; militance; pol4105; pol5185; premier cycle; périodes historiques; régions géographiques; thématiques

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Mind the Gaps: Intersex and (Re-productive) Spaces in Disability Studies and Bioethics - Holmes, M. Morgan (Journal of Bioethical Inquiry, 2008)
With a few notable exceptions disability studies has not taken account of intersexuality, and it is principally through the lenses of feminist and queer-theory oriented ethical discussions but not through ‘straight’ bioethics that modes valuing intersex difference have been proposed. Meanwhile, the medical presupposition that intersex characteristics are inherently disabling to social viability remains the taken-for-granted truth from which clinical practice proceeds. In this paper I argue against bioethical perspectives that justify extensive and invasive pre- and post-natal medical interference to eradicate intersex. I argue instead that to constitute the necessary conditions for the recognition of the intersexed child as a person, a life valid in its own right, clinicians must refrain from aggressive interference. Clinical specialists presuppose that intersexed children will be socially disabled and unrecognizable as persons; frustrated by the general failure of traditional interventions to assign a sex, clinicians are now pursuing prenatal technologies, including selective termination, to erase intersex.
Keywords: LGBTQIA2+; approches et analyses; biologie; bioéthique; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; médecine; premier cycle; queer; sciences; soc2014; thématiques; éthique

Intersex: a perilous difference - Holmes, Morgan (Susquehanna University Press, 2008)
As threatening evidence that sex is not the natural basis upon which oppositional gender roles are built, the intersexed are made to disappear into normative categories, thus aligning once again the rightful place of male and female as opposites.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; patriarcat; personnes intersexes; premier cycle; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; violences; violences médicales

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Globalization as Racialized, Sexualized Violence THE CASE OF INDIGENOUS WOMEN - Kuokkanen, Rauna (International Feminist Journal of Politics, 2008)
In my article, I suggest that indigenous women are among the hardest hit by economic globalization – the expansion of markets, trade liberalization and cheapening of labour – and that globalization represents a multifaceted violence against indigenous women. I consider this with the help of two examples. First, I discuss the largely ignored case of missing and murdered Aboriginal women in Canada and how the interlocking systems of oppression (colonization, patriarchy and capitalism) are further intensified by globalization. Second, I examine the death of a Hopi woman, Private Piestewa, in the context of militarization, history of colonization and globalization. I analyse these examples in an intersectional framework that reveals the links between colonization, patriarchy and capitalism all of which inform the current processes of globalization.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; armée états-unienne; canada; capitalisme; cours; discipline; féminicide; globalisation; histoire et politique; intersectionnalité; militarisation; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis

Anishnaabe-Kwe, traditional knowledge, and water protection - McGregor, Deborah (Canadian Woman Studies, 2008)
26CANADIAN WOMAN STUDIES/LES CAHIERS DE LA FEMMEDans cet article, l’auteure partage ses expériences de travail sur les questions environnementales, particulièrement sur celles qui concernent l’eau. Comme mère, comme membre d’un clan, comme membre des Premières Nations et comme professeure, l’auteure se sent responsable du partage de ses connaissances. Cette réflexion est basée sur son travail avec les aînées et les tenants du savoir traditionnel en Ontario, surtout de celui qui se rapporte à l’eau. L’information part de deux projets majeurs dans lesquels elle a été impliquée.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droit; droit de l'environnement; eau; environnement; féminisme autochtone; ontario; point de vue situé; pol4105; premier cycle; pédagogie; périodes historiques; régions géographiques; science politique et droit; sciences de l'éducation; thématiques; transmissions; écoféminisme; écoféminisme amérindien

Critical geographies and the uses of sexuality: deconstructing queer space - Oswin, Natalie (Progress in Human Geography, 2008)
Scholarship on queer geographies has called attention to the active production of space as heterosexualized and has levelled powerful critiques at the implicit heterosexual bias of much geographical theorizing. As a result, critical geographers have begun to remark upon the resistance of gays, lesbians and other sexual subjects to a dominant heterosexuality. But such a liberal framework of oppression and resistance is precisely the sort of mapping that poststructuralist queer theory emerged to write against. So, rather than charting the progress of queer geographies, this article offers a critical reading of the deployment of the notion of `queer space' in geography and highlights an alternative queer approach that is inseparable from feminist, materialist, postcolonial and critical race theories.
Keywords: LGBTQIA2+; approches et analyses; architecture; cours; discipline; espace; géographie; hétéronormativité; premier cycle; queer; résistance; sciences humaines; soc2014; thématiques

Pharmaco‐pornographic Politics: Towards a New Gender Ecology - Preciado, Paul B. (Parallax, 2008)
Keywords: approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; philosophie politique; premier cycle; queer; ressource en ligne; sciences humaines; thématiques

Introduction: Trans-, Trans, or Transgender? - Stryker, Susan; Currah, Paisley; Moore, Lisa Jean (Women's Studies Quarterly, 2008)
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; histoire; identités LGBTQIA2+; lit4700; premier cycle; ressource en ligne; sciences humaines; thématiques; transféminisme; études trans*

Black atlantic, queer Atlantic: Queer imaginings of the middle passage - Tinsley, Omise'eke Natasha (GLQ: A Journal of Lesbian and Gay Studies, 2008)
Qu'est-ce que cela signifierait pour les études queer et sur la diaspora africaine de théoriser que l'Atlantique noir a toujours été un Atlantique queer ? Quelle nouvelle géographie – ou mieux, océanographie – des identités sexuelles, genrées, transnationales et raciales pourrait émerger d'une lecture queer des dislocations transocéaniques entre l'Afrique et la Caraïbe ? Cet article examine la diaspora africaine canonique et les textes théoriques queer en dialogue avec des textes créatifs récemment publiés qui imaginent les relations queer entre les kidnappés africains dans les cales des navires négriers. Ces textes créatifs, selon moi, théorisent plus largement l'espace conceptuel à la fois pour repenser les histoires sexuelles et raciales submergées et pour commenter les intersections entre la diaspora africaine et les expériences queer à une époque contemporaine de réfugiés haïtiens, de travailleurs dominicains transnationaux, et des militants « homosexuels » antillais internationaux. Les textes examinés comprennent celui de Paul GilroyBlack Atlantic (1993), Gender Trouble de Judith Butler (1990), Erzulie's Skirt d'Ana-Maurine Lara (2006) et Map to the Door of No Return de Dionne Brand (2001).
Keywords: afrique; amériques; approches et analyses; caraïbes; cours; discours dominant; fem3300; genre; identités LGBTQIA2+; premier cycle; queer; racisme; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's University Press, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Section: xxi, 157 pages
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques